2017
DOI: 10.3233/jad-170131
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Bilingualism Compared to Monolingualism to the Risk of Cognitive Decline or Dementia: A Systematic Review and Meta-Analysis

Abstract: Abstract:BACKGROUND: Bilingualism may contribute to cognitive reserve, protect against

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 28 publications
0
78
2
Order By: Relevance
“…Over the lifetime, adaptive changes required to represent and control the use of two languages may increase resilience to degenerative changes in the aging brain (for a counter‐view based on a meta‐analysis of selected retrospective and prospective studies, see Ref. ). Putative resilience may arise in one of two ways: it may be increased by neural reserve (adaptive changes that lead to more gray and/or white matter volumes or white matter integrity as compared to controls) or by means of neural compensation (to compensate better the loss of neural structure as compared to controls with less loss of brain structure) .…”
Section: Bilingualism Healthy Aging and Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the lifetime, adaptive changes required to represent and control the use of two languages may increase resilience to degenerative changes in the aging brain (for a counter‐view based on a meta‐analysis of selected retrospective and prospective studies, see Ref. ). Putative resilience may arise in one of two ways: it may be increased by neural reserve (adaptive changes that lead to more gray and/or white matter volumes or white matter integrity as compared to controls) or by means of neural compensation (to compensate better the loss of neural structure as compared to controls with less loss of brain structure) .…”
Section: Bilingualism Healthy Aging and Neuroprotectionmentioning
confidence: 99%
“…As noted above, evidence in favor of the neuroprotective effects of bilingualism has not gone without challenge. For instance, the analysis of the mini‐mental state examination data (a measure of global cognitive functioning) in a longitudinal Australian cohort found that education, but not bilingualism per se , was predictive of cognitive decline . However, neuroprotective effects arguably depend on the precise patterns of bilingual language use that were not documented in the cohort data.…”
Section: Bilingualism Healthy Aging and Neuroprotectionmentioning
confidence: 99%
“…Some have shown people who are bilingual scoring higher on cognitive tests and being diagnosed with dementia at a later age but others have not . A recent systematic review and meta‐analysis found no difference in the risk of developing dementia in prospective studies comparing bilinguals versus monolinguals . All studies included in the meta‐analysis were conducted in northern America.…”
Section: Introductionmentioning
confidence: 99%
“…Our circumspect conclusion takes this into account and states that “bilingualism is complex and that simply speaking two languages does not protect from cognitive decline or enhance executive function. The precise pattern of language use in bilingual speakers may be critical and certainly such information is necessary to more fully disentangle the longer‐term neuroprotective effect of bilingualism.” Mukadam et al further investigated this topic in their systematic review of bilingualism and cognitive decline and again concluded that bilingualism itself is not protective against cognitive decline when analyses from cohort studies are appropriately adjusted for education and socioeconomic status . We would welcome future research that could measure the more fine‐grained effects of bilingualism, comparing, for example, bilinguals who frequently switch between different languages and those who use their languages in separate environments.…”
mentioning
confidence: 99%